2015
DOI: 10.1016/j.mib.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking transcription coupled DNA repair

Abstract: Nucleotide excision repair (NER) is an evolutionarily conserved, multistep process that can detect a wide variety of DNA lesions. Transcription coupled repair (TCR) is a sub-pathway of NER that repairs the transcribed DNA strand faster than the rest of the genome. RNA polymerase (RNAP) stalled at DNA lesions mediates the recruitment of NER enzymes to the damage site. In this review we focus on a newly identified bacterial TCR pathway in which the NER enzyme UvrD, in conjunction with NusA, plays a major role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…At present, the global relevance of pervasive transcription is still enigmatic. A new and provocative hypothesis was recently proposed (Kamarthapu & Nudler, 2015). Pervasive transcription might permit genomic surveillance of DNA lesions.…”
Section: Mechanisms Toward Functions?mentioning
confidence: 99%
“…At present, the global relevance of pervasive transcription is still enigmatic. A new and provocative hypothesis was recently proposed (Kamarthapu & Nudler, 2015). Pervasive transcription might permit genomic surveillance of DNA lesions.…”
Section: Mechanisms Toward Functions?mentioning
confidence: 99%
“…Although the number of asRNAs with identified function is limited (reviewed by Thomason & Storz, 2010;Georg & Hess, 2011;Schultze et al, 2014), it is generally assumed that asRNAs could play a role in the regulation of gene expression via a variety of mechanisms, such as transcriptional interference, transcription attenuation, and modulation of degradation by nucleases and of ribosome binding (Thomason & Storz, 2010). Recently, a novel role of pervasive transcription in the surveillance of genome damage and efficient nucleotide excision repair was proposed (Kamarthapu & Nudler, 2015). However, it has also been suggested that pervasive transcription may have no functional role and be a form of transcriptional noise (Peters et al, 2012;Raghavan et al, 2012).…”
Section: Suppression Of Pervasive Transcriptionmentioning
confidence: 99%
“…Global genomic repair (GGR) detects lesions throughout the genome, whereas transcription-coupled repair (TCR) is initiated when RNA polymerases are blocked by lesions on the template DNA strand. TCR was first described in rodent cells, then in human cells, E. coli , yeast and in other organisms (reviewed in Ganesan et al 2012; Hanawalt and Spivak 2008; Kamarthapu and Nudler 2015; Mullenders 2015), including halophilic archaea as recently reported (Stantial et al 2016), and was defined as the recognition and repair of DNA lesions or structures occurring in the transcribed strand of active genes. Interestingly, the first observation of TCR (Mellon et al 1987) was possible because the model lesions utilized in those initial experiments, cyclobutane pyrimidine dimers (CPDs), are repaired inefficiently in non-transcribed DNA in hamster cells, facilitating detection of the faster repair of transcribed strands by TCR.…”
Section: Introductionmentioning
confidence: 99%